The effect of high pressure treatment on the quality of chicken breast meat - Marušić, Nives, inženjerka prehrambene tehnologije; Ježek, Damir; Markov, Ksenija; Frece, Jadranka; Ćurić, Duška; Medić, Helga (2020)
In the present work, the effect of high pressure processing (HPP) (0, 100, 200 and 300 MPa) and different treatment time (5 and 10 minutes) on the moisture uptake, cooking yield, colour and texture, as well as microbial population of chicken breast fillets was investigated. The application of high hydrostatic pressure resulted in a modification of quality parameters of chicken breast meat. By increasing pressure and time of the treatment the moisture uptake was reduced: samples treated with 300 MPa for 10 min had the lowest moisture uptake values. Cooking yield was not affected by HPP treatments. Increased pressure affected the colour by increasing L*, a* and b* values (only HPP treatment of 100 MPa in duration of 5 and 10 minutes did not affect colour of chicken breast meat). Lower pressures (100 and 200 MPa) tenderized, whereas elevated pressure (300 MPa) increased hardness in chicken breast fillets. Higher level of pressure (300 MPa) reduced bacteria count by about 3.0 – 5.3 log (CFU/g), depending on the microorganism and duration of the process.
Bibliografija: str. 80-81.
Abstract.
Keywords: Piletina -- Meso -- Sigurnost hrane -- Kvaliteta mesa -- Visokotlačna obrada